ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA ECERAN BERAS DI INDONESIA TAHUN 2018-2021 - Made Widiantara, I Gusti Agung; Sri Budhi, Made Kembar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.09.TAHUN.2024, 2024)
This study aims to analyze the factors that affect the retail price of rice in Indonesia such as rice production, rice consumption and rice imports. The objectives of this study are 1) analyzing the effect of simultaneous rice production, consumption and import on the retail price of rice in Indonesia. 2) analyze the effect of rice production, consumption and imports partially on the retail price of rice in Indonesia. The analysis technique used in the study is multiple linear regression analysis. The data used is secondary data with 136 observations consisting of a combination of time series data and cross section data. The results of this study found that the level of rice production and consumption had a negative and significant effect on the retail price of rice in Indonesia, while rice imports did not have a significant but negaitf effect on the retail price of rice in Indonesia. the dominant influential free variable with the highest Standardized Coefficients Beta value is shown in the rice production variable.